Rethinking resistance : revolt and violence in African history - Abbink, J.; Bruijn, Mirjam de, 1962-; Walraven, Klaas van, 1958- (African dynamics, 2003)
This work covers the subject of resistance. Were political forms of resistance directed at the imposition or ending of colonial rule or at African elites profiting from the onset of capitalist relations of production? This work aims to answer this question and more.